2003
DOI: 10.1029/2003jd003398
|View full text |Cite
|
Sign up to set email alerts
|

Application of the antenna theory model to a tall tower struck by lightning

Abstract: [1] The interaction of lightning with the 553-m high CN Tower in Toronto is modeled using the antenna theory model. A simple lossless wire structure is used to represent the tower. The return-stroke channel is modeled as a lossy vertical antenna attached to the tower top. The lossy antenna and the wire structure representing the tower are assumed to be fed at their junction point by a voltage source. The voltage waveform of this source is selected so that the source current resembles a typical lightning curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 18 publications
5
57
0
1
Order By: Relevance
“…Furthermore, the lightning channel is represented by a lossy vertical wire antenna, neglecting the corona effect. Note that the resistance per unit channel length is assumed to be 0.07 Ω/m, as in [19], the wire radius is a = 10 cm. For the sake of simplicity, the current wave along the channel is assumed to propagate at the velocity of light although the realistic current propagation velocity is by the factor of two or three less than in the model used in this work.…”
Section: Numerical Solution Of An Integral Equation Set For Overhead mentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the lightning channel is represented by a lossy vertical wire antenna, neglecting the corona effect. Note that the resistance per unit channel length is assumed to be 0.07 Ω/m, as in [19], the wire radius is a = 10 cm. For the sake of simplicity, the current wave along the channel is assumed to propagate at the velocity of light although the realistic current propagation velocity is by the factor of two or three less than in the model used in this work.…”
Section: Numerical Solution Of An Integral Equation Set For Overhead mentioning
confidence: 99%
“…Within the framework of engineering models, the presence of a tall object has been considered by the use of a uniform, lossless transmission line representation [12,13]. The AT models [14][15][16][17][18][19] have been mostly applied in the analysis of lightning strikes to CN tower in Toronto, e.g. [18] or similar towers, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Models based on this approach are referred to as electromagnetic models (e.g., Rakov and Uman [3]). In these models (e.g., Podgorski and Landt [4], Moini et al [5], Kordi et al [6], Baba and Rakov [7]), lightning return stroke channel is represented by a vertical conductor of nonzero thickness. It has been shown that a current pulse attenuates as it propagates along such a conductor, even in the absence of ohmic losses, when it is excited at its bottom by a lumped voltage source (Bantin [8]; Kordi et al [9], [10]; Baba and Ishii [11]) or by a lumped current source (Grcev et al [12], and Baba and Rakov [7]).…”
Section: Introductionmentioning
confidence: 99%